Rule Of Reason dan Perse Ilegal dalam Penyelesaian Sengketa Ekonomi Syariah Perspektif Hukum pada Koperasi Syariah di Indonesia - Achmat Hilmi (Prodi Ekonomi Syariah, Fakultas Syariah, Institut PTIQ Jakarta, 2023)
This research aims to analyze the resolution of Sharia economic disputes in Sharia cooperatives using a contemporary Islamic legal approach, specifically through the Rule of Reason and Per Se Illegal approaches. The research method employed is a qualitative approach with a case study of several Sharia cooperatives in Indonesia. Data were obtained through in-depth interviews with relevant parties and analysis of documents related to the resolution of Sharia economic disputes. The findings indicate that common dispute resolution mechanisms used by Sharia cooperatives include consultation, mediation, and arbitration, with the Rule of Reason and Per Se Illegal principles serving as the legal analysis foundation. The Sharia Supervisory Board plays a significant role in ensuring compliance with Sharia principles in dispute resolution. However, there are some gaps in the implementation of dispute resolution, particularly in the application of fairness and balance principles. These gaps highlight the need for improvements and enhancements in the implementation of Sharia economic dispute resolution in Sharia cooperatives, taking into account the Rule of Reason and Per Se Illegal principles. This research provides insights into the practices and implementation of Sharia economic dispute resolution relevant to the needs and context of Sharia cooperatives in Indonesia, with a focus on the Rule of Reason and Per Se Illegal approaches in legal analysis. The research findings can serve as a basis for more effective policy-making in enhancing the resolution of Sharia economic disputes in Sharia cooperatives, considering contemporary Islamic legal aspects.